ANALISIS KEPUASAN KONSUMEN TERHADAP KUALITAS PRODUK DAN PELAYANAN DENGAN MENGGUNAKAN METODE IMPORTANCE PERFORMANCE ANALYSIS (Studi Kasus di Angkringan Jinggo Bu Jero, Kediri Tabanan) - Wulan Darini, Made Anggray; Hartiati, Amna; Wiranatha, Agung Suryawan (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI, 2018)
The aims of this study were to determine attributes considered important by consumers in order to achieve customer satisfaction, determine the attributes that need to get priority from the company to be improved in order to achieve customer satisfaction and know the level of satisfaction or level of consumer suitability of products and services in Angkringan Jinggo Bu Jero. The research was conducted at Angkringan Jinggo Bu Jero. The sample used is 96 respondents using purposive sampling method. Questionnaires are directly distributed to respondents. The data obtained were analyzed using Importance Performance Analysis method. The result of this research showed that attribute with highest level of consumer satisfaction for product quality is the portion of food that fit with the level of compliance equal to 114,91%. The attribute with the lowest level of consumer satisfaction for product quality is always concerned with the hygiene of the product with a suitability level of 83.04%. Attribute with the highest level of customer satisfaction for service quality is always pay attention to the interests of consumers with a level of suitability of 102.49%. Attribute with the lowest level of customer satisfaction for service quality is beverage processing using good quality materials with a level of suitability of 92.29%. Attributes that must get priority for the product is always concerned with product hygiene. The attributes that must get priority for service are the consumers can easily submit their complaints and suggestions. Keywords: Consumer Satisfaction, Importance Performance Analysis, Nasi Jinggo, Angkringan Jinggo Bu Jero